Cost per responder analysis in patients with secondary hyperparathyroidism on dialysis treated with cinacalcet. (2nd August 2013) - Belozeroff, Vasily; Lee, Andrew; Tseng, Spring; Chiroli, Silvia; Campbell, Jonathan D.
Abstract: Background: Growing financial pressure on US dialysis providers requires economic efficiency considerations. The objective of this study was to examine short-term economic efficiencies of a cinacalcet-based treatment approach for secondary hyperparathyroidism. Methods: This study retrospectively assessed cost per biochemical response of the OPTIMA trial. OPTIMA was conducted in end-stage renal disease patients to compare biochemical control in patients receiving cinacalcet in addition to vitamin D sterols and phosphate binders vs patients receiving vitamin D sterol and phosphate binders alone. It explored three laboratory measurement response definitions from baseline to week 23: (1) decreases in parathyroid hormone (PTH) ≥30%; (2) PTH ≤ 300 pg/ml; and (3) PTH ≤ 300 pg/mL, calcium <9.5 mg/dL and phosphorus <5.5 mg/dL. Medication use and costs were measured to calculate average costs and incremental cost per responder. Stratification by lower and higher baseline PTH assessed cost per response by disease severity. Results: There were 38–77% more responders with cinacalcet vs control, depending on response definition. Mean (SD) per patient total medication costs were $5423 ($3698) for cinacalcet and $2633 ($2334) for control, leading to a mean difference of $2790 over 23 weeks. When response was defined as a decrease in PTH ≥ 30% from baseline, the average cost per responder was $11, 266 for control vs $7027 for cinacalcet. The incremental cost per incremental responder ranged from $5186–$9168. Across all response measures, cost per responder was lower in patients with lower baseline PTH. Conclusions: Representing a more efficient allocation of economic resources over the short-term, cinacalcet-based treatment algorithm led to a lower cost per biochemical response, particularly in patients with lower disease severity, vs vitamin D sterols and phosphate binders alone. These findings should be interpreted alongside the study limitation of converting international trial-based medication utilization into US costs.